Tit for tat or good for evil? Linking customer incivility, hostility, guilt, and employee behaviors - Chen, Chong; Zhang, Mingyu; Zhang, Yihua (Frontiers in Psychology, 2023)
The existing literature overemphasizes the negative effects of customer incivility on service employees. However, the positive effects of customer incivility on employee behavior are rarely mentioned. Drawing on affective events theory and attribution theory, we used a moderated dual-mediator causal model to explore the effect of customer incivility on employees’ revenge behavior and customer-oriented behavior through hostility and guilt, and the moderating role of customer blame attribution. An empirical study with a sample of 366 employee-supervisor pairs and two-wave, two-source data indicated that customer incivility positively impacts revenge behavior via employees’ hostility, and this relationship is reinforced by customer blame attribution. In contrast, customer incivility positively impacts customer oriented behavior via employees’ guilt, and this relationship is weakened by customer blame attribution. This study expanded the literature on customer incivility and emotion, and provided significant practical implications for organization on how to help frontline employees deal with customer incivility.